The Promises and Perils of Urban Redevelopment for Land Value Capture in Addis Ababa: the Case of Casa Inchis Redevelopment Project - Yirgalem, Frew (Ethiopian Journal of Social Sciences, 2018)
n 2002, the city government of Addis Ababa launched the Casa Inchis redevelopment project with the dual objectives of eradicating slum and bringing land into profitable use by accommodating commercial and mixed land uses. This paper assessed the extent to which the government managed to capture land value increment by redeveloping Casa Inchis, and examined whether or not the value captured is recycled to recover intervention cost and/or to benefit displaced households. Empirical data was collected during a field visit to the project site. Data sources also include the Casa Inchis LDP, land transactions, compensation and relocation reports, satellite and ground images, urban land policy documents, and interview with officials and experts. It was found out that the redevelopment in Casa Inchis resulted in about five fold increase in land value. Modifying density regulation, land use change and the government's investment in redevelopment were the driving forces for the land value increment. Evidences also suggest that the monetary benefit of the redevelopment was nearly twice that of its cost. Hence, the findings of this study suggest that the city government was successful in capturing part of the land value increment in Casa Inchis. Nevertheless, the study also revealed that the value capture endeavor had some gloomy aspects. First, the projectÂ  was implemented at the expanses of displaced households. Only 32% of households were eligible for compensation; the majority had to move away for nothing despite residing in Casa Inchis for over 25 years. Second, by transfering the land free of lease payment, the project resulted in the loss of revenue (estimated to be close to USD 20 million) which could have been collected from lease payment to recover intervention cost and benefit displaced households. Third, though the LDP stipulated land sharing and mobilizing land value to relocate households on-site, the project implementers opted for off-site relocation. Along with the lack of political accountability and commitment, the emphasis on revenue generation and city beautification over improving the living condition of slum dwellers seem to be the underlying factors. Fourth, the process was also found to be marred with lack of transparency in plot transfer, preferential treatment of some households over others, and absence of any meaningful obligations on developers despite the government had the legal leverage for doing so. This study emphasizes the imperative for policy makers to appreciate the benefits and properly deal with the challenge ofÂ  designing a 'pro-poor redevelopment' and value capture strategy that not only brings efficiency in land use and eradicates slum but also improves the living conditions of slum-dwellers.